THE EFFECTS OF OBESITY ON FEMALE PATIENTS' REPRODUCTIVE FUNCTION IN IN VITRO FERTILIZATION (IVF) PROGRAMS - Ирина Борисовна Фаткуллина; Альфия Тлешевна Сугурова; Энже Филюсовна Шайхлисламова; Вусала Аладдиновна Садыхова; Танзилла Хамидовна Далаева; Аэллина Александровна Жданова (Мать и дитя в Кузбассе)
Due to the multifaceted impact of obesity on women's reproductive function, as well as the outcomes of assisted reproductive technology (ART) programs, there is an urgent need to study the impact of this disease and find ways to solve this problem in women with infertility planning ART programs.